Crosslinked hyaluronic acid and filler composition containing same
The hyaluronic acid crosslinked body, featuring a critical deformation rate and swollen degree within specific ranges, addresses the issue of swelling in hyaluronic acid fillers by enhancing cohesive and adhesive forces, thereby maintaining volume and morphology post-injection.
Patent Information
- Application Number
- JP2023577285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-17
- Filing Date
- 2022-06-15
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2042-06-15
AI Technical Summary
Current hyaluronic acid fillers face challenges with swelling, which reduces their viscoelasticity and strength, leading to undesirable volume changes and reduced effectiveness during intrabody injection.
A hyaluronic acid crosslinked body with a critical deformation rate of 10% to 100% and a swollen degree of 1% to 100%, utilizing a crosslinker with a difunctional epoxy group, such as 1,4-butanediol diglycidyl ether, to achieve high cohesive and adhesive forces while minimizing swelling.
The crosslinked hyaluronic acid gel maintains its original form and volume post-injection, exhibits high cohesive and adhesive forces, and significantly reduces swelling, ensuring long-term morphology retention and improved biocompatibility.
Smart Images

Figure 0007674529000004 
Figure 0007674529000001 
Figure 0007674529000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a crosslinked hyaluronic acid and a filler composition containing the same, and more specifically, to a crosslinked hyaluronic acid having high cohesive strength and adhesive strength while exhibiting reduced swelling, and a filler composition containing the same. [Background technology]
[0002] Hyaluronic acid (HA) is generally a linear polysaccharide with a high average molecular weight. Hyaluronic acid is a polymer of D-glucuronic acid and N-acetyl-D-glucosamine, and is negatively charged. Hyaluronic acid is found mainly in the extracellular matrix and intercellular matrix, but also exists intracellularly. As such, hyaluronic acid is a substance that already exists in the body, so it is biocompatible and has the property that it is easy to manufacture crosslinked hyaluronic acid hydrogels using crosslinking agents. Therefore, filler products using crosslinked hyaluronic acid have been widely used worldwide since they were introduced to the market in the 1990s as Restylane products by Galderma.
[0003] Currently, hyaluronic acid gels used as fillers are produced by chemically crosslinking natural hyaluronic acid into a network through a crosslinking reaction. Natural hyaluronic acid and certain partially crosslinked hyaluronic acid absorb water until they are completely dissolved in water, but crosslinked hyaluronic acid gels typically absorb a certain amount of water until they are saturated, and thus have a limited swelling degree.
[0004] In addition, filler products using crosslinked hyaluronic acid gel can be classified as monophasic or biphasic. Single-phase crosslinked hyaluronic acid gel has a high viscous modulus and a low elastic modulus. Biphasic crosslinked hyaluronic acid gel has a low viscous modulus and a high elastic modulus. Single-phase crosslinked hyaluronic acid gel and biphasic crosslinked hyaluronic acid gel have different properties in the body. For example, single-phase crosslinked hyaluronic acid gel with a low elastic modulus and a high viscous modulus has excellent cohesive force and is unlikely to be detached from the injected site, but has the property of being able to absorb water in addition, and therefore has the property of continuing to absorb surrounding water in the body. As a result, single-phase crosslinked hyaluronic acid gel generally has the disadvantage of being unable to maintain the original shape injected at the initial stage of injection when injected into the body, and its volume increases compared to the volume previously injected. In contrast, biphasic cross-linked hyaluronic acid gel, which has a high elastic modulus but a low viscosity modulus, can maintain the injected shape for a long period of time with little volume change, but has the characteristics of being easily detached from the injected site and not being able to be distributed evenly throughout the injected site.
[0005] In addition, swelling may occur after hyaluronic acid filler treatment, which refers to the phenomenon in which the hyaluronic acid gel component injected into the body absorbs body fluids from the tissues surrounding the injection site, causing the injected site and the surrounding area to swell. Such swelling is one of the common side effects of filler treatment in that the injected site swells, and is an undesirable phenomenon in that the absorbed water reduces the viscosity, elasticity and strength of the hyaluronic acid gel, which may reduce the effectiveness of the filler injection.
[0006] Therefore, there remains a need for a hyaluronic acid filler that maintains suitable viscoelasticity and gel strength when injected into the body and exhibits minimal swelling when injected into the body. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present disclosure is to provide a crosslinked hyaluronic acid having a critical deformation rate of 10% to 100% and a swelling degree of 1% to 100%.
[0008] Another object of the present disclosure is to provide a filler composition comprising said crosslinked hyaluronic acid. [Means for solving the problem]
[0009] One embodiment of the present disclosure provides a crosslinked hyaluronic acid having a critical deformation rate of 10% to 100% and a swelling degree of 1% to 100%.
[0010] In a specific embodiment, the hyaluronic acid crosslinker also has an average particle size in the range of 50 μm to 150 μm.
[0011] In a specific example, the crosslinked hyaluronic acid has an elastic modulus (G') of 400 Pa to 2,000 Pa.
[0012] In a specific example, the hyaluronic acid crosslinker also has a viscosity modulus (G") of 100 Pa to 600 Pa.
[0013] In a specific example, the hyaluronic acid crosslinker has a compressive strength of 15 N·s to 100 N·s.
[0014] In a specific embodiment, the hyaluronic acid crosslinker has an injection force of 1N to 50N.
[0015] In a specific example, the hyaluronic acid crosslinker can be crosslinked with a crosslinker having a difunctional epoxy group. The crosslinker having a difunctional epoxy group can be one or more selected from the group consisting of 1,4-butanediol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, poly(propylene glycol) diglycidyl ether, poly(tetramethylene glycol) diglycidyl ether, polyglycerol polyglycidyl ether, glycerol diglycidyl ether, triethylene diglycidyl ether, trimethylolpropane triglycidyl ether, ethylene diglycidyl ether, neopentyl glycol diglycidyl ether and 1,6-hexanediol diglycidyl ether.
[0016] Another aspect of the present disclosure provides a filler composition comprising the above-mentioned crosslinked hyaluronic acid.
[0017] In specific examples, the concentration of the hyaluronic acid crosslinker in the filler composition is from 10 mg / mL to 30 mg / mL.
[0018] In an embodiment, the filler composition does not contain additional non-crosslinked hyaluronic acid.
[0019] In an embodiment, the filler composition further comprises a local anesthetic.
[0020] In an embodiment, the filler composition is also loaded into a syringe.
[0021] In an embodiment, the filler composition may be used for one or more applications selected from the group consisting of facial shaping, wrinkle reduction, facial contouring, breast shaping, breast augmentation, genital enlargement, glans enlargement, urinary incontinence treatment, and arthritis treatment. Effect of the Invention
[0022] The crosslinked hyaluronic acid gel according to the present disclosure is characterized by having high cohesive and adhesive strength, and therefore remaining intact at the injection site without detachment, and by reducing the swelling phenomenon after injection. [Brief description of the drawings]
[0023] [Figure 1] This is a graph showing the volume of hyaluronic acid gel injected over time after injection of a crosslinked hyaluronic acid sample into a hairless mouse. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present disclosure generally provides a crosslinked hyaluronic acid having a critical strain of 10% to 100% and a swelling degree of 1% to 100%.
[0025] As used herein, the term "hyaluronic acid" refers to hyaluronan, hyaluronate, or a pharma- ceutically acceptable salt thereof having the chemical formula of Formula 1:
[0026] [ka] In formula 1, n is the number of repeating units. The hyaluronic acid may be derived from any source. The hyaluronic acid may be derived from, for example, an animal or non-animal body. The hyaluronic acid may also be derived from bacteria. The bacteria may be derived from the genus Streptococcus. The genus Streptococcus bacteria may be Streptococcuse qui, S. pyogenes or S. zooepidemicus. The hyaluronic acid may also be commercially purchased.
[0027] The molecular weight of the hyaluronic acid is from 1,000,000 Da to 2,500,000 Da, for example, from 1,000,000 Da to 2,000,000 Da, from 1,500,000 Da to 2,500,000 Da, or even from 1,500,000 Da to 2,000,000 Da.
[0028] The intrinsic viscosity of the hyaluronic acid is 1.0 m 3 / kg to 5.0m 3 / kg, e.g., 1.5m 3 / kg or 4.0m 3 / kg, 2.5m 3 / kg or 4.0m 3 / kg, 2.5m 3 / kg or 3.5m 3 / kg, or 2.5m 3 / kg to 3.0m 3 / kg.
[0029] As used herein, the term "hyaluronic acid crosslinked product" means crosslinked hyaluronic acid, and the terms "hyaluronic acid crosslinked product," "crosslinked hyaluronic acid," and "crosslinked hyaluronic acid" are used interchangeably.
[0030] As used herein, the term "swelling" refers to the phenomenon in which a crosslinked hyaluronic acid gel absorbs water and swells.
[0031] The term "swelling degree" as used herein refers to the ratio of the weight of a completely swollen crosslinked hyaluronic acid gel to the weight of the gel before swelling when the crosslinked hyaluronic acid is immersed in water. The swelling degree can be obtained, for example, by the formula described in the measurement method section below.
[0032] As used herein, the term "critical strain" refers to a measurement index that identifies the deformation rate value required to cause destruction of the internal structure of a material, including linear viscoelastic properties, when a shear deformation rate is applied to the material. In general, crosslinked hyaluronic acid gels are composed of crosslinked hyaluronic acid gels or crosslinked hyaluronic acid gels and solutions, and various internal interaction forces exist within them due to hydrogen bonds, covalent bonds, van der Waals bonds, and physical bonds. The internal interactions are classified as gel-gel, gel-solution, or solution-solution interactions, and since the molecular fluidity of solutions is higher than that of gels and the contact area is smaller than that of gels, the magnitude of the interaction can be seen as gel-gel > gel-solution > solution-solution. In the case of a single phase that exists only in the gel-gel form, it has a relatively high interaction, so it can be expected that the internal structure will be destroyed at even higher deformation rates. In the case of a biphasic structure, since both the gel and the solution exist, the gel-gel interaction is reduced, while the gel-solution and solution-solution interactions are increased. Therefore, the total interaction of the internal structure is expected to be smaller than that of the single phase structure, and the internal structure is expected to be destroyed at a lower deformation rate.
[0033] As a result of the similarity, it is expected that typical single-phase filler products will have strong cohesion properties, while biphasic filler products will have relatively weak cohesion properties compared to single-phase fillers. Cohesion properties can be used as a predictive index of how well an injectable material will form a mass in vivo. To verify this, a comparison was made between biphasic filler products and single-phase filler products in terms of adhesive strength, which is an index for measuring the degree of cohesion, and it was confirmed that the single-phase product had a higher adhesive strength value than the biphasic product.
[0034] The crosslinked hyaluronic acid according to one aspect of the present disclosure shows unexpected properties in that it has a high critical deformation ratio, but a low degree of swelling, like conventional single-phase hyaluronic acid fillers.In addition, the crosslinked hyaluronic acid according to the present disclosure has high cohesive strength and high adhesive strength similar to conventional single-phase fillers, so it is not easily detached from the injection site, and can maintain the injected shape for a long period of time due to its high elastic modulus (G').
[0035] The hyaluronic acid crosslinked material according to the present disclosure has (i) a critical deformation rate of 10% to 100%, for example, 10% to 50%, 10% to 30%, or 10% to 40%, for example, 10% to 50%, for example, 10% to 30%, while having a swelling degree of 1% to 100%, for example, 1% to 90%, 1% to 80%, 1% to 70%, 1% to 60%, 1% to 50%, 10% to 60%, 20% to 60%, 30% to 60%, 40% to 60%, 40% to 50%, or 50% to 60%.
[0036] The hyaluronic acid crosslinked body may have an average particle size (μm) of 50 μm to 150 μm, for example, 60 μm to 150 μm, 70 μm to 150 μm, 80 μm to 150 μm, 90 μm to 150 μm, 60 μm to 140 μm, 60 μm to 130 μm, 60 μm to 120 μm, or 60 μm to 100 μm.
[0037] The hyaluronic acid crosslinked body has (iii) an elastic modulus (G') of 400 Pa to 2,000 Pa, for example, 500 Pa to 1,900 Pa, 600 Pa to 1,800 Pa, or 600 Pa to 1,700 Pa.
[0038] The hyaluronic acid crosslinked material also has (iv) a viscosity coefficient (G") of 100 Pa to 600 Pa, for example, 120 Pa to 500 Pa, 150 Pa to 450 Pa, or 160 Pa to 350 Pa.
[0039] The hyaluronic acid crosslinked body may also have a (v) compression force of 15 N·s to 100 N·s, for example, 20 N·s to 90 N·s, 25 N·s to 80 N·s, or 30 N·s to 75 N·s.
[0040] The hyaluronic acid crosslinker may also have (vi) an injection force of 1N to 50N, for example, 3N to 45N, 4N to 40N, or 7N to 35N.
[0041] In one specific example, the hyaluronic acid crosslinked product satisfies the requirement (i) above, and also satisfies requirements 1, 2, 3, 4 or 5 among the requirements (ii) to (vi) above.
[0042] The crosslinked hyaluronic acid according to the present disclosure may be produced, for example, by a process including, but not limited to, the following steps: (a) adding a crosslinking agent to hyaluronic acid dissolved in an alkaline aqueous solution to perform crosslinking; (b) subjecting the crosslinked gel to dialysis, washing and / or swelling; (c) grinding; and (d) Filling the syringe.
[0043] In the process steps, the order of steps (b) through (d) may be changed or may be repeated two or more times, for example, a grinding step may be additionally performed between steps (a) and (b) in addition to step (c), or may be performed only in step (c), or may be performed only between steps (a) and (b) instead of step (c).
[0044] Also, in addition to the above-mentioned steps (a) to (d), the method may further include other additional steps, for example, a step of adding an anesthetic as described below, and / or a step of performing high-temperature steam sterilization. For example, the step of adding an anesthetic may be added between the above-mentioned steps (b) and (c), or between the above-mentioned steps (c) and (d). The step of performing high-temperature steam sterilization may be added between the above-mentioned steps (c) and (d), or after step (d).
[0045] In step (a), the alkaline aqueous solution may be, but is not limited to, NaOH, KOH, or preferably NaOH aqueous solution. When NaOH aqueous solution is used, the concentration is 0.1% (w / w) to 2.5% (w / w), for example, 0.1% (w / w) to 2.0% (w / w), or 0.5% (w / w) to 1.0% (w / w).
[0046] The concentration of hyaluronic acid dissolved in the alkaline aqueous solution is also 10% (w / w) to 25% (w / w), for example, 10% (w / w) to 20% (w / w), or 10% (w / w) to 15% (w / w).
[0047] In the step (a), the crosslinking agent may have a polyfunctional group. The crosslinking agent may have a difunctional epoxy group. The crosslinking agent having a difunctional epoxy group may be one or more selected from the group consisting of 1,4-butanediol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, poly(propylene glycol) diglycidyl ether, poly(tetramethylene glycol) diglycidyl ether, polyglycerol polyglycidyl ether, glycerol diglycidyl ether, triethylene diglycidyl ether, trimethylolpropane triglycidyl ether, ethylene diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether.
[0048] The crosslinking reaction may be carried out at room temperature or higher, for example, 20°C to 40°C, 25°C to 40°C, or 30°C to 40°C, and the reaction time may be 24 hours or less, for example, 10 hours to 24 hours, 15 hours to 24 hours, or 15 hours to 20 hours.
[0049] In the step (b), the dialysis refers to a step of mixing the crosslinked gel with a dialysis solution containing a specific buffer solution, such as NaCl solution, KOH solution, PBS solution, etc., in a dialysis membrane or dialysis container, dialyzing, washing, and swelling the dialyzed gel. The series of dialysis, washing, and swelling steps may be repeated two or more times. Through the series of dialysis, washing, and swelling steps, the unreacted crosslinker may be removed and / or the pH and / or osmotic pressure of the crosslinked gel may be adjusted.
[0050] In step (c), the grinding may be carried out using a grinder at 1,000 to 10,000 rpm, for example, 2,000 to 9,000 rpm, 3,000 to 8,000 rpm, 4,000 to 7,000 rpm, 5,000 to 9,000 rpm, or 5,000 to 8,000 rpm, for 60 seconds or more, for example, 60 to 100 seconds, 70 to 120 seconds, 80 to 140 seconds, 90 to 160 seconds, 100 to 180 seconds, or 120 to 240 seconds.
[0051] Another embodiment provides a filler composition comprising the above-described crosslinked hyaluronic acid.
[0052] In the composition, the final concentration of the crosslinked hyaluronic acid gel is 10 mg / ml or more, 15 mg / ml or more, 18 mg / ml or more, or even 19 mg / ml or more. For example, the concentration of the crosslinked hyaluronic acid is 10 mg / ml to 30 mg / ml, 12 mg / ml to 28 mg / ml, 14 mg / ml to 26 mg / ml, 16 mg / ml to 24 mg / ml, 16 mg / ml to 20 mg / ml, or about 18 mg / ml.
[0053] The composition also does not contain additional non-crosslinked hyaluronic acid. "Additionally containing" non-crosslinked hyaluronic acid means that non-crosslinked hyaluronic acid is artificially added to the crosslinked hyaluronic acid, and "not containing additional non-crosslinked hyaluronic acid" means that non-crosslinked hyaluronic acid is not artificially added to the crosslinked hyaluronic acid.
[0054] The composition may further include an anesthetic. The anesthetic may be a local anesthetic. The anesthetic may be ambucaine, amolanone, amylocaine, benoxinate, benzocaine, betoxycaine, biphenamine, bupivacaine, butacaine, butamben, butanilicaine, butethamine, butoxycaine, tetracycl ... e), carticaine, chloroprocaine, cocaethylene, cocaine, cyclomethycaine, dibucaine, dimethysoquin, dimethocaine, diperodon, dicyclonine, ecgonidine, ecgonine, ethyl chloride chloride), etidocaine, beta-eucaine, euprocin, fenalcomine, formocaine, hexylcaine, hydroxytetracaine, isobutyl p-aminobenzoate, leucinocaine mesylate, levoxadrol, lidocaine, mepivacaine, meprylcaine, metabutoxycaine, methyl chloridechloride), myrtecaine, naepaine, octacaine, orthocaine, oxethazaine, parethoxycaine, phenacaine, phenol, piperocaine, pyridocaine, polidocanol, pramoxine, prilocaine, procaine, propanocaine The active ingredient may be, but is not limited to, one or more selected from the group consisting of cocaine, pyrrocaine, ropivacaine, salicylalcohol, tetracaine, tolycaine, trimecaine, zolamine, and salts thereof.
[0055] The composition is also free of pharma- ceutical active substances selected from the group consisting of proteins, glycosaminoglycans other than hyaluronic acid, and hydroxypropylmethylcellulose.
[0056] The composition may also be packaged in a syringe.
[0057] The composition may also be used for tissue repair in an individual.
[0058] In the composition, the individual is also a mammal. The mammal may be a human, a dog, a cat, a cow, a pig, a rat or a sheep.
[0059] The composition is also for use in one or more applications selected from the group consisting of facial shaping, wrinkle reduction, facial contouring, breast shaping, breast augmentation, genital enlargement, glans enlargement, urinary incontinence treatment, and arthritis treatment.
[0060] The composition may further include pharma- ceutically acceptable carriers, excipients, and diluents. The carrier may include, for example, water or a buffer. The buffer may be such that the pH of the solution does not change appreciably with the addition of the components of the composition. The composition may be an aqueous liquid composition. The composition may be an aqueous buffered composition. The pH of the aqueous buffered composition may be in the physiological pH range, for example, between about 6.0 and 8.0. The pH may be adjusted by adding a suitable acid or base, such as HCl, Na2CO3, or NaOH. In one embodiment, the aqueous buffered composition may include phosphate buffered saline (PBS). In another embodiment, the aqueous buffered composition may include tris(hydroxymethyl)aminomethane (Tris). In some embodiments, additional solutes, such as sodium chloride, calcium chloride, and potassium chloride, may be added to adjust osmolarity and ion concentration.
[0061] The composition is also sterile.
[0062] The composition may be contained in a container. The container may be a syringe. The composition may be pre-loaded into a syringe prior to use. The composition may be administered into a pre-loaded syringe.
[0063] Another aspect provides a device comprising the composition described above. The device may also be a pre-filled syringe. The device may also be sterile.
[0064] Another aspect provides a kit comprising the pre-filled syringe described above, said kit also comprising a manual containing information concerning administration of said composition.
[0065] Another embodiment provides a method for bulking tissue of an individual, comprising administering to the individual a therapeutically effective amount of the composition described above. The method may be for augmenting, repairing or strengthening an individual's tissue or for filling a body cavity. In this respect, volume augmentation may be a long-lasting increase in volume due to the components forming the filler composition. The components forming the filler composition may not undergo rapid diffusion. In the method, the "composition" and the "individual" are as described above. The administration may be into the skin, such as into the dermis, or into a joint cavity. In the method, the administration may be into the skin, such as into the dermis, via a syringe, e.g., a pre-filled syringe. In the method, the administration may be into the skin, e.g., into the dermis, of 0.1 to 50 ml, 0.5 to 30 ml, 0.5 to 20 ml, 0.5 to 15 ml, or 0.8 to 12 ml per administration. In the methods, the administering may also be administering the composition once per 3 or more months, once per 4 or more months, once per 5 or more months, once per 6 or more months, once per 12 or more months, or once per 18 or more months.
[0066] The present invention will be described in more detail below through examples. However, these examples are for illustrative purposes only and the scope of the present invention is not limited to these examples.
[0067] Working Example Measurement method (1) Critical strain measurement method The critical deformation ratio was measured by a strain-sweep test. Specifically, a DHR-2 rheometer (TA Instruments) was operated. The deformation sweep test was performed by setting the instrument temperature to 25°C, attaching a 25 mm diameter geometry, and performing calibration. An appropriate amount of sample was loaded in the center between the upper and lower geometries of the instrument's Peltier plate. The sample was overloaded in a sufficient amount so as not to run out, and an appropriate amount was loaded so that the sample would not be attached to the side and upper surfaces of the geometry even if the remaining part outside the area of the lower part of the geometry was scraped off. After the geometry was lowered to a set interval, it was confirmed whether the sample was well filled under the geometry, and the remaining part outside the geometry was scraped off and removed (trimming). Thereafter, the elastic modulus value measured at each deformation ratio was measured when strains of 0.1 to 1,000% were applied to the sample using the geometry. From the measured values measured by the rheometer, values of the deformation rate % (strain (%)) and elastic modulus (Pa: storage modulus) were taken, and GraphPad Software's GraphPad Prism (Prism8, version 8.4.3 (686)) was used to convert the deformation rate % (strain (%)) value to log(strain (%)) using the transform function built into the program. In order to easily confirm the minimum deformation rate % (strain (%)) among the obtained values, a smooth graph of the change in elastic modulus (Pa: storage modulus) against the log(strain (%)) value was calculated using the smooth function built into the program, and then the value was converted to the deformation rate % (strain (%)) before taking log(strain (%)) using the transform function. From the data obtained in the above process, the change in the elastic modulus (Pa: storage modulus) value according to the deformation rate % (strain (%)) was confirmed, and the deformation rate % (strain (%)) of the minimum elastic modulus value was defined as the critical deformation rate.
[0068] (2) Swelling degree measurement method The hyaluronic acid gel was added to the conical tube and weighed, and the initial weight was recorded. 5.0 mL of PBS solution (pH 7.4) was added to the conical tube, vortexed for 1 minute, mixed homogeneously, sealed completely, and incubated at room temperature for 24 hours to swell the hyaluronic acid gel. Then, 200 μL of Alcian Blue solution was added to the swollen hyaluronic acid gel in the conical tube, vortexed for 1 minute, and incubated at room temperature for 30 minutes to stain the hyaluronic acid gel. It was centrifuged at 14,000 g for 10 minutes at 4° C. to precipitate the hyaluronic acid gel, and the supernatant was carefully removed with a pipette. Then, to remove the dye from the hyaluronic acid gel, 5.0 mL of PBS solution (pH 7.4) was added, vortexed for 1 minute, and centrifuged at 14,000 g for 10 minutes at 4° C. The supernatant was carefully removed with a pipette, and the procedure of adding PBS and centrifuging was carried out twice more. The swollen hyaluronic acid gel thus obtained was weighed, and the swelling degree was calculated according to the following formula: TIFF0007674529000002.tif11170 (3) Average particle size measurement method The average particle size is measured using a Particle Size Analyzer S3500 manufactured by Microtrac. The average particle size is measured by adding a sample to a solvent and using laser diffraction analysis. The solvent is distilled water. Before the measurement, the sample inlet is thoroughly washed with distilled water, and the refractive index of the distilled water and the refractive index of the sample are input as 1.33 and 1.37, respectively, and the type of the sample is set as transparent particles having irregular shapes. Before the measurement, the sample inlet of the device is filled with distilled water, and the sample is put into a tube, etc., and diluted with an excess of distilled water, and the sample is thoroughly dispersed using a vortex, etc., and then put into the device to perform the measurement. Among the measurement results, the average particle size (D50) was used as data.
[0069] (4) Viscoelasticity measurement method A DHR-2 rheometer (TA Instruments) was operated. The viscoelasticity test was performed by setting the instrument temperature at 25°C, installing a 40 mm diameter geometry, and performing correction. An appropriate amount of sample was loaded in the center between the upper and lower geometries of the Peltier plate of the instrument. A sufficient amount of sample was overloaded so that the sample was not insufficient, and an appropriate amount was loaded so that the sample did not touch the side and upper surfaces of the geometry. After the geometry was lowered to a set interval, it was confirmed whether the sample was filled under the geometry, and the remaining sample outside the geometry was removed by scraping. Then, the geometry was periodically applied with a shear strain at a specific frequency with a constant deformation rate to the sample, and the storage modulus value and the loss modulus value at a frequency of about 0.1 Hz were defined as elasticity and viscosity, respectively, in the modulus values obtained from the above.
[0070] (5) Adhesive force measurement method The adhesion was measured as follows. A DHR-2 rheometer (TA Instruments) was operated. The adhesion test was performed by setting the instrument temperature to 25° C., installing a 40 mm diameter geometry, and performing calibration. An appropriate amount of sample was loaded in the center between the top of the Peltier plate of the instrument and the bottom geometry. A sufficient amount of sample was overloaded so as not to run out of sample, and an appropriate amount was loaded so that it did not touch the side and top surfaces of the geometry. After the geometry was lowered to a set distance, it was confirmed whether the sample was well filled under the geometry, and the remaining sample outside the geometry was removed by scraping. Then, the geometry gap was set to a height of 1,000 μm, and the force applied to the geometry was measured when the lower Peltier plate was pulled in the vertical axis direction at a constant speed of 100.0 μm / s for 180 seconds. The maximum force at the moment when the initial sample fell was measured due to the adhesion force of the sample between the geometry and the Peltier plate, and this force was defined as the adhesion force.
[0071] (6) Compressive force measurement method A DHR-2 rheometer (TA Instruments) was run. The compression force test was performed with the instrument temperature set to 25°C, a 25 mm diameter geometry attached, and calibration performed. Approximately 1 mL of sample was loaded in the center between the upper and lower geometries of the Peltier plate of the instrument. After the geometry was lowered to the set interval, the geometry was rotated at a slow speed to adjust the sample to be centered on the geometry basis. The geometry was then lowered at a constant speed of 13.33 μm / s from 2,500 μm to the 900 μm position, while the force applied to the geometry was measured. The compression force was defined as the value corresponding to the area under the graph, which is the integral value of the graph, when the force measured from the start to the end of the test was plotted on the Y axis and the time of movement on the X axis.
[0072] (7) Injection force measurement method The injection force measurement was performed using a Mecmesin Multitest 2.5-i Universal Testing Machine. The load cell used to measure the force applied to the instrument was equipped with an appropriate load cell with a tolerance higher than the injection force measurement range. A syringe containing a sample was placed under the instrument load cell, and an injection needle was attached to the syringe. A push rod with a flat end was placed on the syringe so that a constant force could be applied when the load cell applied force. After adjusting the distance until the load cell part reached the end of the push rod, the push rod part was pushed using the load cell at a speed of 12 mm / min to measure the applied force. In the initial and end parts of the measurement, the pressure value generated when the sample flows into the injection needle is lower than the pressure applied when the syringe is inserted. In addition, when the injection of the injection material is almost completed, there are cases where the force is continuously applied even though the sample is not present, and in such cases, the applied force is a force that is not related to the injection force of the sample. Therefore, the injection force was defined as the average of the injection force values measured in the middle of the syringe filling liquid excluding the value corresponding to the portion where the sample flows into the injection needle and the portion where the injection is almost completed, i.e., the initial injection force value and the final injection force value.
[0073] Examples 1 and 2: Preparation of cross-linked hyaluronic acid A crosslinked hyaluronic acid having a critical deformation rate of 10% to 100% and a swelling degree of 1% to 100% was prepared as follows.
[0074] First, a 1% (w / w) NaOH solution was prepared. 5g of sodium hyaluronate (IV 2.2 to 3.0) was mixed into the prepared 1% NaOH solution to make the solution 13.00% (w / w), and then stirred to dissolve thoroughly. Here, "IV" indicates intrinsic viscosity. 0.630g of butanediol diglycidyl ether (BDDE) (Sigma-Aldrich) was added to the solution, and the solution was stirred until well mixed, and then removed. The crosslinking reaction was carried out at 40°C for 16 to 20 hours to prepare a crosslinked hyaluronic acid gel.
[0075] Next, the obtained crosslinked gel was put into a dialysis membrane and sealed, and dialysis was performed using 1mol / kg NaCl aqueous solution and 1x PBS aqueous solution as the dialysis solution to remove unreacted crosslinker. After the dialysis was completed, the loss rate was taken into account by the weight of the sodium hyaluronate initially put in, and the content was corrected using 1x PBS so that the final concentration of sodium hyaluronate removed was 18mg / mL. At this time, the content was corrected to 3mg / mL in the case of lidocaine hydrochloride hydrate. As a result, a PBS solution containing about 18mg / mL of crosslinked hyaluronate and about 3mg / mL of lidocaine was prepared. The prepared crosslinked hyaluronan-containing solution was pulverized for 180 seconds at 8,000rpm using a mixer (Retsch GM-200). Then, 1ml of the pulverized crosslinked hyaluronan-containing solution was filled into a glass syringe, and then sterilized with high-temperature steam. The material obtained via such a process was designated Example 1.
[0076] In the case of Example 2, the crosslinked hyaluronic acid-containing solution was prepared in the same manner as in Example 1, except that the solution was ground at 5,000 rpm for 75 seconds using a mixer (Retsch GM-200).
[0077] Comparative Example 1 Comparative Example 1 was prepared in the same manner as in Example 1, except that the crosslinked hyaluronic acid-containing solution was ground for 180 seconds at 2,000 rpm using a mixer (Retsch GM-200).
[0078] Comparative Example 2 and Comparative Example 3 As Comparative Example 2, Allergan's Juvederm Voluma Lidocaine, which is a single-phase crosslinked hyaluronic acid, was used, and as Comparative Example 3, Galderma's Restylane Lyft Lidocaine, which is a biphasic crosslinked hyaluronic acid, was used.
[0079] Experimental Example 1: Measurement of physical properties of cross-linked hyaluronic acid gel The physical properties of the crosslinked hyaluronic acid gel were measured by the methods described in the measurement methods (1) to (7) in the above Examples, and the results are shown in Table 1 below.
[0080] [Table 1] As shown in Table 1, it can be seen that the swelling degree of Examples 1 and 2 is significantly lower than that of Comparative Example 2 (Juvederm Voluma L (Allergan)), which is a conventional single-phase crosslinked hyaluronic acid filler. In the case of Comparative Example 3 (Restylane Lyft L (Galderma)), which is a conventional biphasic crosslinked hyaluronic acid filler, the swelling degree could not be measured due to the problem that the crosslinked hyaluronic acid gel and the solution were not separated during the swelling degree measurement.
[0081] Considering the physical properties in Table 1, it can be seen that Examples 1 and 2 have similar compressive strength and adhesive strength to conventional single-phase fillers, and are unlikely to come off at the injection site, and have low swelling, so that swelling phenomenon is significantly reduced when injected into the body. In addition, the fact that they have a high elastic modulus (G') shows that they can maintain the injected shape for a long period of time.
[0082] Experimental Example 2: Measurement of the effect of lifting and volumizing when cross-linked hyaluronic acid is applied to animals: lifting and volumizing test Fifty-two 6-week-old female hairless mice (SKH1-hr) (20±3 g) were obtained from Orient Bio (Republic of Korea) and acclimatized for more than one week. The acclimatized mice were anesthetized by intraperitoneal injection of a mixed anesthetic of ketamine (100 mg / kg) and Rompun (10 mg / kg), and then 0.1 mL of each of the above-mentioned Examples 1 and 2 and Comparative Examples 1 and 3 was subcutaneously injected into the dorsal region site using a glass syringe. After injection, the weight of each individual was measured on the designated date. The height of the injection site, the maximum length, and the volume of the injected material were measured using Primos 5.8E (Canfield Scientific Inc, NJ, USA). At the same time, the injection site was observed with the naked eye and photographed.
[0083] Figure 1 shows the volume change observed up to 42 weeks after intradermal injection of hyaluronic acid gel. As shown in Figure 1, in the case of Comparative Example 1, which is a conventional single-phase crosslinked hyaluronic acid gel, the volume increased significantly at the beginning of injection (increased by about 100% compared to the initial injection volume) and decreased significantly over time, whereas in Examples 1 and 2, the volume change was small or almost nonexistent compared to the beginning of injection (increased by about 10% compared to the initial injection volume). It can also be seen that in Examples 1 and 2, the volume loss was relatively small over the course of 24 weeks.
[0084] In summary, it was confirmed that Examples 1 and 2 had little swelling in the early stages after injection, were able to maintain their original volume at the time of injection, and showed little volume change up to 24 weeks after injection, demonstrating excellent in vivo durability and biocompatibility.
Claims
1. A crosslinked hyaluronic acid having a critical strain of 10% to 30%, a swelling degree of 40% to 60%, an average particle size of 50 μm to 150 μm, and an elastic modulus (G′) of 400 Pa to 2,000 Pa.
2. The hyaluronic acid crosslinked material according to claim 1, wherein the compressive force is from 15 N·s to 100 N·s.
3. The hyaluronic acid crosslinked material according to claim 1, which is crosslinked with a crosslinking agent having a bifunctional epoxy group.
4. The hyaluronic acid crosslinked material according to claim 3, wherein the crosslinking agent having a bifunctional epoxy group is at least one selected from the group consisting of 1,4-butanediol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, poly(propylene glycol) diglycidyl ether, poly(tetramethylene glycol) diglycidyl ether, polyglycerol polyglycidyl ether, glycerol diglycidyl ether, triethylene diglycidyl ether, trimethylolpropane triglycidyl ether, ethylene diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether.
5. A filler composition comprising the hyaluronic acid crosslinker according to claim 1 .
6. The composition according to claim 5, wherein the concentration of the hyaluronic acid crosslinker is 10 mg / mL to 30 mg / mL.
7. The composition of claim 5, which does not contain additional non-crosslinked hyaluronic acid.
8. The composition of claim 5 further comprising a local anesthetic.
9. The composition of claim 5 which is packaged in a syringe.
10. The composition according to claim 5, which is for use in one or more applications selected from the group consisting of facial shaping, wrinkle reduction, facial contouring, breast shaping, breast augmentation, genital enlargement, glans enlargement, urinary incontinence treatment, and arthritis treatment.
Citation Information
Patent Citations
Crosslinked hyaluronic acid gel and its production
JP1993140201A
Crosslinked hyaluronic acid, hyaluronic acid hydrogel, and method for producing crosslinked hyaluronic acid and hyaluronic acid hydrogel
WO2020116999A1
Injectable homogeneous gels comprising multiple forms of hyaluronic acid and methods for manufacturing thereof
WO2020194294A1
Method of cultivating plants and system therefor
WO2021075963A1